Contribuição da telessaúde para o atendimento na Atenção Primária à Saúde: Uma análise a partir das ações vinculadas à Secretaria Estadual de Saúde do Estado do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Information and communication technologies (ICTs) have played an important role in the area of health in Brazil, promoting significant advances in the provision of services and access to health care. Telehealth stands out as an innovative approach to providing health services at a distance, using ICTs as facilitating tools, resumed in the State of Paraná after the pandemic period. Considering the potential of ICTs in the health area, this dissertation has as its theme telehealth actions and their relationship with Primary Health Care (PHC). It is known that the APS is the originator of care, the gateway, the first contact of users with the Unified Health System (SUS). In view of this, it is believed that this dissertation will be able to help users, health professionals and managers to visualize the contributions of telehealth, benefits and challenges that are presented in the face of this innovative approach in the context of the state of Paraná. For its construction, the critical dialectical method was used to guide the path of thought, from the theoretical framework to the analysis of results. Therefore, the research started from the following guiding questions: Are there telehealth actions linked to the State Health Department of the state of Paraná? How are these actions organized? What is the contribution of these actions to PHC care? Thus, this qualitative research was developed, which is classified as exploratory and descriptive, and the universe of the research was delimited to the State of Paraná and the sample to the municipalities belonging to the first health regional of the state. A semi-structured interview with a professional from the Paraná State Health Department was used as a data collection instrument, as well as the application of a questionnaire to six PHC professionals from the municipalities of the first health regional. Data collection was aimed at achieving the general objective of analyzing the implementation of telehealth in the Health Regions of the State of Paraná and its contribution to PHC care in municipalities and specific areas, which are: Mapping the initiatives and use of telehealth linked to Health Regional Offices of the State of Paraná; identify, from the scope of telehealth, which are the actions developed in the health regions; and to analyze whether the implementation of telehealth, in the health regions, can contribute to the assistance in the health PHC of the municipalities. Finally, the responses of these professionals were analyzed following the methodology of content analysis.
Keywords: Telessaúde; Atenção Primária à Saúde; Acesso à Saúde; Telehealth; Primary Health Care; Health Access; CNPQ::CIENCIAS SOCIAIS APLICADAS